Heterogeneous Methylation and Deletion Patterns of the INK4a/ARF Locus Within Prostate Carcinomas - Konishi, Noboru (American Society for Investigative Pathology, 2002)
To elucidate the role of p53/p16(INK4a)/RB1 pathways in prostate carcinogenesis, we analyzed the p14(ARF), p16(INK4a), RB1, p21(Waf1), p27(Kip1), PTEN, p73, p53, and MDM2 gene status of multiple areas within 16 histologically heterogeneous prostate carcinomas using methylation-specific polymerase chain reaction, differential polymerase chain reaction, and immunohistochemistry. All focal areas examined had Gleason scores ranging from 1 to 5. Methylation of either PTEN or p73 was undetected in any sample, whereas expression of MDM2 seemed to be an independent event within small foci of 4 of 16 tumors. Loss of p14(ARF), p16(INK4a), RB1, and p27(Kip1) expression correlated with homozygous deletion or promoter hypermethylation. One carcinoma showed co-deletion of both p14(ARF) and p16(INK4a) in two of five areas examined; two areas within another tumor demonstrated concurrent hypermethylation of the promoter regions of the same genes. Focal hypermethylation of RB1, p21(Waf1), and p27(Kip1) was detected within two, two, and three tumors, respectively. These findings indicate that both genetic and epigenetic events occur independently in intratumor foci and further suggest hypermethylation-induced loss of gene function may be as critical as specific genetic mutations in prostate carcinogenesis.